2010
DOI: 10.1097/ico.0b013e3181ca3668
|View full text |Cite
|
Sign up to set email alerts
|

Meibomian Gland Duct Distortion in Patients With Perennial Allergic Conjunctivitis

Abstract: Perennial AC is associated with increased meibomian gland duct distortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 7 publications
3
41
0
2
Order By: Relevance
“…In the present study, most of the morphologic changes of the meibomian glands started from the orifice side. Moreover, we recently reported that meibomian gland duct distortion, which is the initial stage of the changes in the meibomian glands, is associated with allergic conjunctivitis [33]. Taken together, the mechanism for meibomian gland loss in eyes with longterm anti-glaucoma eye drops may be due to chronic and subclinical inflammatory and allergic reactions causing lid margin abnormalities, followed by the stagnation of meibum and resulting in changes of the meibomian glands that lie adjacent to the conjunctiva.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, most of the morphologic changes of the meibomian glands started from the orifice side. Moreover, we recently reported that meibomian gland duct distortion, which is the initial stage of the changes in the meibomian glands, is associated with allergic conjunctivitis [33]. Taken together, the mechanism for meibomian gland loss in eyes with longterm anti-glaucoma eye drops may be due to chronic and subclinical inflammatory and allergic reactions causing lid margin abnormalities, followed by the stagnation of meibum and resulting in changes of the meibomian glands that lie adjacent to the conjunctiva.…”
Section: Discussionmentioning
confidence: 98%
“…Because patients with AC frequently rub their eyes, the rubbing could induce MG distortion. Furthermore, because distortion was confined to the upper eyelid and was not present in the lower eyelid, the rubbing quite possibly led to the distortion of the MG ducts of the upper eyelid [8].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in our recent study [8], the meibum score was significantly higher in perennial AC patients with MG distortion than in perennial AC patients without MG distortion. According to a previous report, distortion occurs in the first stage of morphological changes of the MG [10].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with AC may have morphological changes of the MGs. Chronic inflammation may induce papillary formation, mucus discharge, conjunctival hyperaemia and tear film instability [47][48][49]. One study comparing 55 patients with AC (diagnosed by papillary reaction and itchy sensation) and 47 healthy volunteers found that the frequency of meibomian duct distortion was significantly greater in patients with AC (45 %) than in controls (8.5 %).…”
Section: Concurrent Allergic or Contact Lens-related Conjunctivitismentioning
confidence: 97%
“…Furthermore, meibum scores (a measure of increased pressure needed to express meibum) and superficial punctate keratopathy scores were significantly higher in the AC group. It is hypothesized that chronic allergy and inflammatory changes in the conjunctival tissue may place pressure on the MGs, causing morphological changes and, in turn, decreased quality of the meibum [47]. Moreover, patients with AC tend to rub their eyes, which could also cause morphological changes.…”
Section: Concurrent Allergic or Contact Lens-related Conjunctivitismentioning
confidence: 99%